2020
DOI: 10.3390/ani10112108
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Behavioral Responses by Mammals and Fish to Zoo Visitors Highlight Differences between Individual Animals

Abstract: The impact that humans have on zoo animals can vary based on the species of animal, exhibit design, and individual differences in behavioral responses. We independently analyzed data from 10 never-published studies that examined the impact of zoo visitors on zoo animal behavior. Of the 16 species studied, 90.9% of the mammal species and 60.0% of the fish species demonstrated a change in at least one behavior based on zoo visitor abundance or visitor behavior (e.g., noise, solicitation of interactions from zoo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…The range in visitor number and the potential impact this may have on the animals' behaviour and welfare spurred research into this area, with the results outlining the complex and multifaceted nature of this topic [10]. The impacts of zoo visitors can vary between facilities, between enclosures within facilities [11], and even between individual animals [12][13][14]. There are many factors which can impact the valence of the experience of visitors near to animal enclosures, including zoo visitor behaviour, enclosure design, presence or absence of enrichment, past experiences of individuals, and individual rearing history [10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The range in visitor number and the potential impact this may have on the animals' behaviour and welfare spurred research into this area, with the results outlining the complex and multifaceted nature of this topic [10]. The impacts of zoo visitors can vary between facilities, between enclosures within facilities [11], and even between individual animals [12][13][14]. There are many factors which can impact the valence of the experience of visitors near to animal enclosures, including zoo visitor behaviour, enclosure design, presence or absence of enrichment, past experiences of individuals, and individual rearing history [10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies of visitor effects have found evidence for all of these effects, with varying and sometimes conflicting results. An independent analysis by Boyle et al (2020) determined that, out of 16 different species, 90% of mammals and 60% of fish had at least one behavioral change associated with visitor abundance or behavior. Visitor presence and density have been associated with increased levels of abnormal behavior or aggression across several species, including mandrills (Mandrillus sphinx), Diana monkeys (Cercopithecus diana), lion-tailed macaques (Macaca silenus), jaguars (Panthera onca), black-capped capuchins (Sapajus apella), and western lowland gorillas (Gorilla gorilla gorilla) (Chamove et al, 1988;Mallapur et al, 2005;Sellinger & Ha, 2005;Sherwen, Harvey, et al, 2015;Stoinski et al, 2012;Wells, 2005).…”
Section: __________________________________________________________________________________mentioning
confidence: 99%
“…Visitor effects should also be considered on an individual basis, as different individuals can have varying behavioral responses to the same environmental stimuli (Boyle et al, 2020;Hashmi & Sullivan, 2020;Kelly et al, 2015;Stoinski et al, 2012). Zoos have largely been moving towards a welfare assessment model that emphasizes the importance of individual-based monitoring and care (Kagan et al, 2015).…”
Section: __________________________________________________________________________________mentioning
confidence: 99%
“…Whereas in the past, zoos' goals may have been mutually exclusive, the advent of environmental enrichment, interactive visitor interpretive programs, and naturalistic exhibits have made the fulfillment of these goals possible. Education can serve as a means of unifying zoo goals; educated and engaged visitors can perhaps contribute to animal welfare by following instructions on how to engage in species-specific behavior that can decrease stress on animal residents (Birke, 2002;Boyle et al, 2020;Lee, 2015;Rabb, 2004).…”
Section: ______________________________________________________________________________mentioning
confidence: 99%